Harmonic Knife New Haemostatic Procedure In Thyroid Surgery - Al-Ali, Thamer T. (AL-Kindy College Medical Journal, 2019)
Background: Thyroid operation needs very meticulous haemostasis to have minimal morbidity and mortality.Objectives: Assessment of harmonic knife in open thyroid surgery as anew haemostatic procedure .Type of the study: Cross-sectional study.Methods: This study had been conducted at Alkindy teaching hospital in Baghdad city from the 1st of May 2013 to the 1st of January 2017  on 229  goiterous patients who needs thyroidectomy(36 males,193 females),divided in 2 groups according to the haemostatic procedure used during their operations, Group A (15 males,85females)using the usual conventional surgery(pick, tie &cut), Group B (21males,108 females) using harmonic knife as haemostatic procedure and compare the results according to time of surgery, amount of discharge in the drain during the first 24 hours post operatively ,the incidence of recurrent nerve palsy and the remote post operative hypocalcaemia (3months post operation) .Results: It shows that thyroid surgery (thyroidectomy) by using harmonic knife as haemostatic procedure is shorter in duration [mean67.22 minutes] with less blood loss in thedrain [mean 64.96cc] and less incidence of hypocalcaemia in remote post operative period [3.8%] in comparison to the results of the usual conventional thyroidectomy procedures (mean duration 82.02 minutes, mean blood loss in the drain 111.13cc & incidence of hypocalcaemia is 7%}.Conclusions: Harmonic knife is very safe & beneficial haemostatic device in thyroid surgery.